APPLICATION OF DATA WAREHOUSE FOR ANALYZING THE EFFECT OF FINANCIAL RATIOS ON STOCK PRICES IN CONSUMER NON-CYCLICALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2022 TO 2024 - Oktavian Luthfi Khairan Somali; Muhammad Aghnat Mumtaz; Ahmad Abdul Faqih; Muhammad Jafni Abbas; Rido Dwi Kurniawan; Muh Masri Sari (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to examine the effect of financial ratios on stock prices of primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022 2024 period, utilizing a Data Warehouse as a data integration platform. Secondary data in the form of financial reports and stock prices were processed through an ETL (Extract, Transform, Load) process to produce a structured and consistent historical dataset. Multiple linear regression (OLS) analysis using SPSS was applied to assess the effect of ROA, TATO, DER, and EPS on stock prices. The results showed that all variables had a significant simultaneous effect, but partially only EPS had a significant positive effect. Conversely, ROA, TATO, and DER did not show a significant effect on stock price variations in the primary consumer goods sector. This finding confirms that earnings per share is a key indicator for investors, while asset efficiency and funding structure do not have a direct impact. Furthermore, this study confirms that implementing a Data Warehouse can improve the effectiveness of financial data integration and analysis across periods.